Experimental Study Of The Effect Of Piccolo Tube Pipe On The Air-Conditioning Experimental Rig Humidity - Ahmad Sobri, Ammar Solehi (Universiti Sains Malaysia, 2018)
Air-conditioning systems play an important role in maintaining the indoor built environment and act as a medium to achieve environment pleasant reply. Air conditioning is a process of removing heat and moisture from indoor of an occupied space and generates cool air to the environment such as in homes, offices and building to improve the occupants comfort level. Due to the process of removing moisture from air by air conditioning process, the indoor humidity level can be reduced drastically. Lack of moisture in the air can contribute to discomfort in residential areas. Low humidity acts as the main problem because cold air may not able to hold as much moisture as warm air. The lower the temperature, the less water can exist in the vapor state. Problems occurred while in low humidity which include discomforts from dry skin, dry nasal passages, irritated eyes and even damage to furniture and flooring. The most effective way to deal with low humidity level inside indoor is by using a humidifier which can be installed in the HVAC system. The humidifier adds moisture to air and provide humid climate thus achieve thermal comfort level. In this research study, installation of humidity system into air conditioning system is done, by ultrasonic humidifier as a device that produce mist or water vapor, thus increase moisture in the air in the HVAC system. This research also has been carried out to investigate the effect of piccolo hole diameter size on percentage of relative humidity (RH) with variation speed of air flow. The diameter of piccolo hole size is 5mm, 7mm, 10mm and 12mm respectively. The flow of air is produced by axial fan with speed of 1ms¯¹, 3ms¯¹ and 5ms¯¹ in HVAC experimental rig. Results show increasing percentage of RH as diameter of piccolo hole size increase at lower speed of air flow. As the speed increase, higher speed of air flow can reduce and cancels out the effect of water vapor produced by ultrasonic humidifier in the HVAC duct due to low size of the fine mist water particles produce by ultrasonic humidifier, (approximately around 1 micron in size), thus give lower percentage of RH reading in HVAC test section.